Agricultural Land Control Based On The Regulation Of The Minister Of Agrarian And Spatial Planning/ Head Of The National Land Agency Of The Republic Of Indonesia Number 18 Of 2016 Concerning Control Of Agricultural Land Tenure - Sunardi, Sunardi; Suratman, H.; Mahmud Hanafi, Wildan (Universitas Islam Malang, 2025)
Abstract: Control of Agricultural Land Tenure. Aims to control the use of agricultural land for housing or other functions other than agriculture. This is a problem, what if a citizen has land with agricultural status, then there are many things that have to go through until it can be divided and sold to other parties. The formulation of the problem of agricultural land division is based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 18 of 2016 concerning Control of Agricultural Land Tenure and the legal consequences if the division does not use the Site Plan issued by the Regency and City Governments. This research is normative research with a statutory and conceptual approach as a result of research on the Process of Dissolving Agricultural Land Based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 18 of 2016 concerning Control of Tenure of Agricultural Land, if the author analyzes the legal system theory then , After the regulation was issued, it aimed to control agricultural land which would be converted into residential land, so that it was limited by this regulation, in theory the authority of the BPN was the institution appointed by the state to carry out control over the conversion of land, by cooperating with the relevant agencies. each district and city, among other things, by determining the RT RW of the city/district, with regard to the process of splitting agricultural land based on the authority of BPN, the applicant must submit a PERTEK to BPN. If in the RT RW the city is not included in green land then the land is permitted for splitting land plots, On the other hand, if the city/regency RT RW includes green land then the land plot will be rejected and the land will never be able to be submitted for land parcel splitting. Waiting for changes to the new district/city RT RW by submitting it to the central BPN ministry. This is in accordance with the Decree of the Minister of Agrarian Affairs and Spatial Planning/Head of BPN Number 1589/SK-HK.02.01/XII/2021 concerning Determination of Maps of Protected Rice Fields (LSD) in Regencies/Cities. Maps of protected rice fields/agriculture are used as material for The Central Government and Regional Governments are in accordance with their authority in determining sustainable food agricultural land in regional spatial plans and detailed spatial plans. Legal Consequences If the Separation of Agricultural Land Does Not Use the Site Plan Issued by the Regency and City Governments, if the author analyzes the theory of authority, it will be rejected because the set plan is absolutely mandatory for the process of dividing land plots exceeding 5 plots and agricultural land.